Taṣrīf Iṣṭilāhī dan Taṣrīf Lugawī Ṡulāṡī Mujarrad dalam Kitab “Al-Taṣrīf” dan “Amṡilah al-Taṣrīfiyyah”; Studi Komparatif - Istiqomah, Salma Nur; Al Farisi, Mohamad Zaka; Maulani, Hikmah (Aphorisme: Journal of Arabic Language, Literature, and Education, 2024)
This research aims to determine the similarities and differences between the Sulatsi Mujarrad chapter and the two books. This study utilizes a qualitative approach, relying on library research as the main methodology. Based on literature references, documentation, and content analysis were used for the data collection method. In the analysis and interpretation stage of the collected data, the researcher applied the comparative thinking method by comparing two Ṣaraf books. The first book is At-Taṣrīf, while the second Ṣaraf book, which is the object of comparison, is Amṡilah Taṣrīfiyyah. From the results of this research, it was found that there are similarities in terms of the form of taṣrīf and differences in terms of the arrangement of taṣrīf terms and taṣrīf Lugawī. The At-Taṣrīf book has a more complete taṣrīf structure, while the Amṡilah Taṣrīfiyyah book has isim alāt, fi'il madi and mudari majhul and isim maf’ūl which are not found in the taṣrīf structure.